Cyber Public Relations dalam Pembentukan Branding â€œDesa Wisataâ€ di Sidomulyo Kabupaten Jember - Minan Jauhari (Jurnal Al-Hikmah, 2022)
This article places cyber public relations as a perspective in understanding organizational communication activities carried out by the Sidomulyo village government, by utilizing internet technology tools and cyber media as a new space in the context of establishing the "tourism village" branding. In practice, this cyber-based organizational communication displays a lot of content describing the potential of the Sidomulyo rural area as an offer of communication content, and is considered attractive for boosting village tourism. This digital-based communication activity also explores many other potentials, both potential in the economic, social and cultural fields. As a public relations function, this digital communication activity is believed to accelerate efforts to build a brand, maintain trust, understanding, and the image of Sidomulyo Village to the public/wide audience. This article with a virtual ethnographic approach aims to be able to explore the phenomenon of organizational communication that is being carried out by the Sidomulyo village government. So it can be understood that village communication activities carried out using cyber media devices are part of cyber public relations in an effort to establish branding as a "tourist village". While branding as a tourism village is needed by the Sidomulyo village government, it should also be in order to maintain trust, understanding, and the image of Sidomulyo village to the public/wide audience.